Qualitative, Quantitative and Cytotoxic estimation of Phytochemicals in aerial parts of Iraqi Bauhinia variegata - Mais Baqer Mohammed; Monther Faisal Mahdi; Ibrahim S. Abbas (College of Pharmacy / Mustansiriyah University, 2022)
Bauhinia variegata L., is a flowering evergreen small medicinal tree characteristic with an aesthetic appearance and the shape of their flowers which resemble the orchid plant. It is a member of Leguminosae family. Commonly called" Khuf Al-Jamal" as in   Arabic and "Camel's feet" as in English. Quantitative estimation of phenolic compounds using UV spectroscopy. Also, HPLC analysis of lupeol and β-sitosterol content of aerial parts B.variegata. Moreover, the anticancer activity of stem and leaves hexane extract against AMJ-13 cell was performed, which considered one of the first studies around the world of this plant extracts activity against AMJ-13 cell.